Tunable Néel–Bloch Magnetic Twists in Fe3GeTe2 with van der Waals Structure. (29th June 2021) - Peng, Licong; Yasin, Fehmi S.; Park, Tae‐Eon; Kim, Sung Jong; Zhang, Xichao; Nagai, Takuro; Kimoto, Koji; Woo, Seonghoon; Yu, Xiuzhen
Abstract: The advent of ferromagnetism in 2D van der Waals (vdW) magnets has stimulated high interest in exploring topological magnetic textures, such as skyrmions for use in future skyrmion‐based spintronic devices. To engineer skyrmions in vdW magnets by transforming Bloch‐type magnetic bubbles into Néel‐type skyrmions, a heavy metal/vdW magnetic thin film heterostructure has been made to induce interfacial Dzyaloshinskii–Moriya interaction (DMI). However, the unambiguous identification of the magnetic textures inherent to vdW magnets, for example, whether the magnetic twists (skyrmions/domain walls) are Néel‐ or Bloch‐type, is unclear. Here we demonstrate that the magnetic twists can be tuned between Néel and Bloch‐type in the vdW magnet Fe3 GeTe2 (FGT) with/without interfacial DMI. We use an in‐plane magnetic field to align the modulation wavevector q of the magnetizations in order to distinguish the Néel‐ or Bloch‐type magnetic twists. We observe that q is perpendicular to the in‐plane field in the heterostructure (Pt/oxidized‐FGT/FGT/oxidized‐FGT), while q aligns at a rotated angle with respect to the field direction in the FGT thin plate thinned from bulk. We find that the aligned domain wall twists hold fan‐like modulations, coinciding qualitatively with our computational results. Abstract : 2D van der Waals (vdW) magnets provide a unique platform for engineering Néel/Bloch‐type skyrmions with the addition/exclusion of heavy metal capping layers. However, the unambiguous identification of the Néel/Bloch‐type twists inherent to vdW magnets remains elusive. This work measures different magnetic domain q ‐vector alignments under in‐plane magnetic fields and identifies the Néel‐ and Bloch‐type twists existing in the heterostructure Fe3 GeTe2 and the FGT thin plate, respectively.